Comparison of translucency and flexural strength of fiber-reinforced composite resin materials - Karatas, Ozcan; Bilgic, Rabia; Gul, Pinar; Ozakar Ilday, Nurcan (Annals of Medical Research, 2021)
Aim: The purpose of this study was to compare translucency values and flexural strength of composite resin materials reinforced with two different fibers.Materials and Methods: In this study, two direct composites (Clearfil Majesty Esthetic and Posterior) and an indirect composite (Tescera) used with a non-fiber control group and two fiber-reinforced (EverStick glass fiber and Ribbond polyethylene fiber) composite groups. Thirty specimens were obtained from the entire composites with dimensions of 25×2×2mm3. Translucency parameter values of the specimens were obtained using a spectrophotometer. The flexural strength (MPa) of the specimens was then determined by a three-point bending test at a rate of 1 mm/min until fracture occurred in the specimen using a universal tester. Data were analyzed by Two Way ANOVA and Tukey HSD multiple comparison test (α=0.05).Results: Ribbond group showed similar translucency parameter values with the control group in all composite materials, but the EverStick group showed significantly lower than the control group (p 0.001). The highest mean flexural strength values were seen in the Clearfil Majesty Posterior control group, while the lowest values were seen in the Clearfil Majesty Esthetic Ribbond group. The mean flexural strength values of the control groups for each composite were found statistically significantly higher than the fiber groups.Conclusion: The fiber addition to composite resins may affect the optical and mechanical properties of the restoration. This effect varies depending on the structural properties of composite resin and fiber. This situation should be taken into consideration in the restoration.